Valoración de las aguas residuales en Israel como un recurso agrícola: consideraciones a tomar en cuenta para la gestión del agua en el Perú - Quipuzco Ushñahua, Lawrence Enrique (2004)
Projections made by scientists on the water situation point to Peru as one of the regions most threatened by the scarcity of water resources by 2025. Droughts in various regions, the progressive loss of glaciers, contamination of the coastal basins , the overexploitation of water resources, the irresponsible use of the water resource due to poor irrigation practices, the increasing demand for water in densely populated cities, are problems that are affecting today in those places in Peru where the water resource scarce. The measures to counter water scarcity will depend a lot on the right decisions made by the State and the rulers. Some experiences developed in the State of Israel can be taken into consideration for water management in Peru. The State of Israel planned and carried out intensive long-term Research and Development efforts to integrate wastewater into the country's water resources. The primary objective of wastewater treatment in Israel is not only intended to protect public health, but also aims to protect the environment and recycle wastewater in agriculture. Wastewater is often viewed as a waste, a nuisance, a risk to public health. The Israeli approach holds that WASTEWATER CONSTITUTES A RESOURCE, ESPECIALLY AN AGRICULTURAL RESOURCE. In Peru, properly treated wastewater can provide a valuable source of water for non-potable uses. The combined practice of wastewater treatment systems and rational agricultural irrigation as used in Israel would mean an economically possible strategy to develop a crucial water source for Peruvian agriculture.